Making education inclusive - Walton, Elizabeth Lockhart; Moonsamy, Sharon (Cambridge Scholars Publishing, 2015)
Exclusionary pressures and practices are pervasive in education, despite the clamour for more inclusive education. Even as classrooms worldwide become more diverse, education is unlikely to become inclusive without deliberate efforts to dismantle exclusion and enable inclusion. This book is a compilation of contributions to the conversation about what these efforts might entail. The conversation has its origins in the Making Education Inclusive Conference held in 2013, which brought together academics and practitioners from Southern Africa and other countries. Given the expectation that teache.